1993
DOI: 10.1002/ijc.2910550608
|View full text |Cite
|
Sign up to set email alerts
|

Expression and shedding of ICAM‐1 in bladder cancer and its immunotherapy

Abstract: Intercellular adhesion molecule-1 (ICAM-1) is one of 3 major ligands for the beta 2 integrin leucocyte function-associated antigen-1 (LFA-1). Several reports have emerged describing soluble forms of ICAM-1 in association with normal and pathological states (e.g., malignancy). In this study we have identified the secretion of soluble ICAM-1 in tissue culture supernatants from bladder tumour monolayers and in the urine of patients receiving intravesical BCG immunotherapy for superficial bladder cancer. In vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
2
29
0
3
Order By: Relevance
“…Elevated amounts of a biologically active form of sI-CAM is detected in serum, cerebrospinal fluid, synovial fluid, urine and sputum in pathologies with an underlying inflammatory status, like autoimmune and degenerative diseases [213][214][215] and tumor pathogenesis [216,217] . Different reports point to various cell sources of sICAM in health and pathologies, including endothelial cells [218] , peripheral blood mononuclear cells, keratinocytes, epidermoid carcinoma cell lines, melanoma cells [219] and tumors [216,217,220] . sICAM can be secreted spontaneously or after specific inductions [220] .…”
Section: Intercellular Adhesion Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated amounts of a biologically active form of sI-CAM is detected in serum, cerebrospinal fluid, synovial fluid, urine and sputum in pathologies with an underlying inflammatory status, like autoimmune and degenerative diseases [213][214][215] and tumor pathogenesis [216,217] . Different reports point to various cell sources of sICAM in health and pathologies, including endothelial cells [218] , peripheral blood mononuclear cells, keratinocytes, epidermoid carcinoma cell lines, melanoma cells [219] and tumors [216,217,220] . sICAM can be secreted spontaneously or after specific inductions [220] .…”
Section: Intercellular Adhesion Moleculementioning
confidence: 99%
“…Different reports point to various cell sources of sICAM in health and pathologies, including endothelial cells [218] , peripheral blood mononuclear cells, keratinocytes, epidermoid carcinoma cell lines, melanoma cells [219] and tumors [216,217,220] . sICAM can be secreted spontaneously or after specific inductions [220] . Limited data demonstrate that some but not all MSCs are a source of sICAM.…”
Section: Intercellular Adhesion Moleculementioning
confidence: 99%
“…When CD54 binds to its ligands LFA-1 and Mac-1 on the surface of T lymphocytes, it plays an essential role as a signal transmitter of immune response, which mediates tumor cytotoxicity (17). It has been reported that CD54 expression on the surface of tumor cells increases the susceptibility of such tumor cells to lymphocyte-mediated tumor cytotoxity through the CD54/ LFA-1 system (18,19). Maruo et al suggested that ICAM-1 was overexpressed in cancer cells and released as soluble-ICAM-1, which would promote hematogenous metastasis by suppressing local anticancer immunity (20).…”
Section: Introductionmentioning
confidence: 99%
“…ICAM-1 is constitutively expressed on a variety of inflammatory and immune effector cells and in structural cells, such as: endothelial cells, fibroblasts, and epithelial cells [3]. In addition, ICAM-1 has been detected on the surface of a variety of primary tumours and tumour cell lines, including lymphomas [4], melanomas [5], renal [6], pancreatic [7], bladder [8] and lung carcinomas [9]. Because LFA-1 is expressed on mononuclear phagocytes, cytotoxic T-cells, natural-killer (NK), and lymphokine-activated killer (LAK) cells [1], the expression of ICAM-1 by tumour cells may be involved in the regulation of their susceptibility to cytotoxic activity of autologous and allogeneic defensive cells.…”
mentioning
confidence: 99%